Towards an islamization of housing = Menuju ke arah Islamisasi Perumahan - Spahic, Omer (International Islamic University Malaysia, 2016)
Islamizing housing phenomenon is a very serious issue in the context of the Muslim architectural reality. It requires major contributions and high-spirited concerted efforts of many parties from across the wide spectrum of society: government, educators, practitioners, professional bodies, NGOs, members of the business community, students and the general public. In this paper, the focus is made on the role of education and educators and, to some extent, practitioners. In the process, the remarkable spiritual dimension of housing in Islam, and the importance of its proper handling, both at the conceptual and practical planes for the success of the project of Islamization, are emphasized. Islam distinguishes between the house, as a physical component, and home, as an aura, environment and ambiance generated by the former. In Islam, the house is an institution. It is a family development centre. Muslim architects, planners, structural engineers and final users alike, should perceive the house phenomenon as a sheer means, an instrument, a carrier of the spiritual, not a goal itself. The paper seeks to enhance people’s awareness as to the significance of correctly conceptualizing Islamic housing and how some of the fundamental aspects of its potential revival could be related to the notion of Islamization of knowledge.